2006
DOI: 10.1002/ejic.200501141
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Fluxional Processes of Diphenyl(2‐thienyl)phosphane Derivatives of Triosmium Clusters

Abstract: Thermal treatment of [Os3(CO)12] with diphenyl(2‐thienyl)phosphane, Ph2P(C4H3S), results in the formation of [Os3(CO)12–x{Ph2P(C4H3S)}x] (x = 1–3, 1–3), but no C–H bond activation was observed. Reaction of [H2Os3(CO)10] with diphenyl(2‐thienyl)phosphane at ambient temperature affords [HOs3(μ‐H)(CO)10{Ph2P(C4H3S)}] (4), but when the samereaction is repeated at elevated temperatures, the cyclometallated species [(μ‐H)Os3(CO)9{μ3‐Ph2P(C4H2S)}] (5) and[(μ‐H)Os3(CO)8{μ3‐Ph2P(C4H2S)}{Ph2P(C4H3S)}] (6) are formed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…Furthermore, Vahrenkamp et al [13] have demonstrated that the tris(2-thienyl)phosphine substituted compounds [Ru 3 (CO) 10 {P(C 4 H 3 S) 3 } 2 ] and [Ru(CO) 3 {P(C 4 H 3 S) 3 } 2 ] can be prepared from the ketyl initiated reaction between [Ru 3 (CO) 12 ] and tris(2-thienyl)phosphine. As a part of our studies of the reactivity of triosmium clusters with phosphothiophenes, we report here the reactions of [Os 3 (CO) 12 ] and [Os 3 (l-H) 2 (CO) 10 ] with tris(2-thienyl)phosphine.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Furthermore, Vahrenkamp et al [13] have demonstrated that the tris(2-thienyl)phosphine substituted compounds [Ru 3 (CO) 10 {P(C 4 H 3 S) 3 } 2 ] and [Ru(CO) 3 {P(C 4 H 3 S) 3 } 2 ] can be prepared from the ketyl initiated reaction between [Ru 3 (CO) 12 ] and tris(2-thienyl)phosphine. As a part of our studies of the reactivity of triosmium clusters with phosphothiophenes, we report here the reactions of [Os 3 (CO) 12 ] and [Os 3 (l-H) 2 (CO) 10 ] with tris(2-thienyl)phosphine.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, we recently reported that [Os 3 (CO) 12 ] and [Os 3 (l-H) 2 -(CO) 10 ] react with diphenyl-2-thienylphosphine to give substitution products with the ligand coordinated in monoand bidentate coordination modes via its phosphorus and sulfur atoms and, in addition, C-H cleavage at the thienyl ring of the ligand [12]. Furthermore, Vahrenkamp et al [13] have demonstrated that the tris(2-thienyl)phosphine substituted compounds [Ru 3 (CO) 10 {P(C 4 H 3 S) 3 } 2 ] and [Ru(CO) 3 {P(C 4 H 3 S) 3 } 2 ] can be prepared from the ketyl initiated reaction between [Ru 3 (CO) 12 ] and tris(2-thienyl)phosphine. As a part of our studies of the reactivity of triosmium clusters with phosphothiophenes, we report here the reactions of [Os 3 (CO) 12 ] and [Os 3 (l-H) 2 (CO) 10 ] with tris(2-thienyl)phosphine.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations